A BRIEF HISTORY OF THE DISCOVERY OF THE SU(3) MASS FORMULA AND OTHER SUBJECTS - OKUBO, SUSUMU (Modern physics letters A, 2006)
We give a brief history of the discovery of the SU(3) mass formula and offer a few remarks on the inequality of partial decay rates of particles and their antiparticles.